The Problem-Based Learning Model Assisted by Quizizz Papermode Improves Critical Thinking Ability in Mathematics Learning - Nindi Itsna Fariha; Noening Andrijati (Journal of Education Reseach and Evaluation, 2024)
The low critical thinking ability is caused by the implementation of learning, which is still teacher-centered. This causes students to have a low level of understanding, making it challenging to work on evaluation questions. This research aims to measure the effectiveness of using the problem-based learning model assisted by Quizizz paper mode on students' critical thinking abilities. This type of research is quasi-experimental research. The population of this study was fourth-grade elementary school students. The research sample was selected using random sampling with 33 students. The data collection method is a test. The instrument used to collect data is test questions. The data analysis technique is inferential statistical analysis. The results of the research show that there are significant differences in critical thinking abilities in the learning outcomes between the control class and the experimental class. Student learning outcomes using the Problem-based learning model assisted by Quizzizz paper mode media are higher than those using the conventional learning model. It was concluded that the problem-based learning model assisted by Quizizz paper mode media could improve critical thinking. The research implies that applying the Problem-based learning model assisted by Quizzizz Paper mode effectively improves students' critical thinking abilities.